2016
DOI: 10.1007/s00253-016-7797-9
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and characteristics of partial nitrification granular sludge in a sequencing batch reactor inoculated with heterotrophic granules

Abstract: The aim of this study was to develop a simple operation strategy for the cultivation of partial nitrification granules (PNGs) treating an autotrophic medium. For this strategy, aerobic granular sludge adapted to high concentration organics removal was seeded in a sequencing batch reactor (SBR) with a height/diameter ratio of 3.8, and the ratio of organics to the ammonia nitrogen-loading rate (C/N ratio) in the influent was employed as the main control parameter to start up the partial nitrification process. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Additionally, it was easy to distinguish them, and it was found that this was typical bacteria for the different functioning bacteria. For the phosphorus removal bacteria, they were short and rod-shaped, which could be seen directly from the SEM observations, which was similar to Wang et al's experiment [36]. It was observed that the abundances of Betaproteobacteria and Alphaproteobacteria were the highest in the bacteria community (the same as our results), and their SEM observations had large amounts of rod-shaped bacteria.…”
Section: Cod Removalssupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, it was easy to distinguish them, and it was found that this was typical bacteria for the different functioning bacteria. For the phosphorus removal bacteria, they were short and rod-shaped, which could be seen directly from the SEM observations, which was similar to Wang et al's experiment [36]. It was observed that the abundances of Betaproteobacteria and Alphaproteobacteria were the highest in the bacteria community (the same as our results), and their SEM observations had large amounts of rod-shaped bacteria.…”
Section: Cod Removalssupporting
confidence: 91%
“…Dechloromonas (3.74% and 2.48%) and Simplicispira (4.47% and 3.21%) were the most common DPAOs for the biological wastewater treatment, which could use NO 3 − -N as the electron acceptor in an anoxic environment for oxidized organic matter [41][42][43], and their abundances both decreased after 0.5 h of the critical aerobic phase. Zoogloea was an easily adapted bacteria because they could adjust themselves either in an aerobic environment or anoxic environment for nitrifying and denitrifying [36,44]. Although the unique phenomenon had not occurred after 0.5 h, the abundance of Zoogloea was mildly enhanced (from 4.87% to 5.77%), which guaranteed the DNRA for NO 3 − -N removal [26].…”
Section: Sludge Structure and Microbial Community Compositionmentioning
confidence: 99%
“…Four representative granule samples (S1-S4) belonging to the different size fractions (Fractions I-IV) were obtained for the microbial community analysis, which was conducted by highthroughput pyrosequencing using MiSeq technology (Illumina, US), as described by Wang et al [20]. In order to enhance the DNA extraction, the different size granules were preprocessed by ultrasound at 1 W/ml for 5 min in an ice bath, respectively [18].…”
Section: Dna Extraction Pcr and Pyrosequencingmentioning
confidence: 99%
“…However, it is not always the case that the low air pressure facilitated the high SND efficiency. The previous experimental results show that the specific NH 4 + ‐N removal rate increased from 4.98 to 9.26 g/(m 2 d) when air pressure increased from 2 to 20 kPa in an MABR with a biofilm thickness of approximately 600 μm . In addition, Li et al .…”
Section: Resultsmentioning
confidence: 79%